2009
DOI: 10.11130/jei.2009.24.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Welfare Effects of the East African Community Customs Union's Transition Arrangements on Uganda

Abstract: Regional trade arrangements are becoming an increasingly popular vehicle for the promotion of trade and growth. In East Africa the previously defunct East Africa Customs Union has been resurrected to improve trade between Kenya, Tanzania and Uganda. To facilitate the development of the East African Community, transitional arrangements have been put in place to liberalise inter and intra-regional trade. Using a partial equilibrium approach this paper quantifies and evaluates the trade and welfare effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Castro, DeRocha and Kraus (2004) in a later study on the trade and revenue impacts of the EACCU using a partial equilibrium model and 2002 data, suggested that the whole region would likely experience modest decline in customs revenue. This was confirmed by Khorana et al (2009), who observed a notable loss of revenue and a lower welfare effect caused by reduction and eventual elimination of tariffs with Kenya. Unfortunately their study is limited to Kenya and Uganda and ignores the other member states, perhaps due to data availability corstraints.…”
Section: Literature Reviewsupporting
confidence: 64%
“…Castro, DeRocha and Kraus (2004) in a later study on the trade and revenue impacts of the EACCU using a partial equilibrium model and 2002 data, suggested that the whole region would likely experience modest decline in customs revenue. This was confirmed by Khorana et al (2009), who observed a notable loss of revenue and a lower welfare effect caused by reduction and eventual elimination of tariffs with Kenya. Unfortunately their study is limited to Kenya and Uganda and ignores the other member states, perhaps due to data availability corstraints.…”
Section: Literature Reviewsupporting
confidence: 64%
“…The results obtained in this study are similar to results by [15] and [5]. Both Studies use a SMART-WITS partial equilibrium model to estimate the effect of the EAC customs union on trade and revenue effects on Uganda.…”
Section: Resultssupporting
confidence: 77%
“…The model uses Armington assumption of product differentiation which assumes that the source of imports for any given product encourage imperfect substitution. The partial equilibrium model used in this study is similar to the model used by [1] and [5] who estimates the effect of the EAC customs union on trade, revenue and welfare on EAC partner states. In addition to [1] and [5] work, this study investigates trade and revenue effects under the EAC framework and evaluates alternative trade liberalization scenarios with the DRC and Sudan which are both Uganda's key trade partners.…”
Section: The Partial Equilibrium Model and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…SMART assumes that there is full transmission of price changes when tariff distortions are introduced (eliminated). The exact expressions for this effect are included in Laird and Yeats () and others (Jammes & Olarreaga, 2005; Khorana, Kimbugwe, & Perdikis, ; Sadni Jallab, Lahsen Abdelmalki, & Sandretto , ), which considers the import demand and export supply functions for any given pair of countries for the product subject to the tariff.…”
Section: Economic Rationale Behind Our Impact Analysismentioning
confidence: 99%